Marine renewable energies Prospective foresight study for 2030 - Lacroix, Denis; Lamblin, Véronique; Paillard, Michel (éditions Quae, 2009)
The ocean is a huge reservoir of renewable energy sources, such as wind, currents, tides, waves, marine biomass, thermal energy, osmotic power, and so on. Like other maritime nations in Europe, France enjoys significant potential to develop these energy sources, especially overseas. In March 2007, Ifremer's chairman launched a prospective foresight study on these energies for the time horizon of 2030. With support from the Futuribles consulting group, twenty French partners representing the main stakeholders in the sector carried out this work. Their objective was to identify the technologies, specify the socio-economic prerequisites for them to emerge and be competitive and assess their respective impacts on power sources and the environment. What was learned from this study can be applied well beyond France, at a time when a European maritime strategy is taking shape.